Perlindungan Anak dalam Perspektif Hukum Islam: Tinjauan atas Hak dan Kewajiban Orang Tua - Rafiqah, Lailan; Simbolon, Parlindungan; Ridwan, M Sulaiman (Journal of Legal Sustainability, 2025)
This study aims to analyze the concept of child protection from the perspective of Islamic law, with a focus on the rights and responsibilities of parents toward their children. Child protection is a fundamental aspect in Islam, encompassing the fulfillment of physical, emotional, and educational needs, as well as protection from violence and neglect. The method used in this study is a qualitative approach through library research, analyzing verses from the Qur’an, the sayings of the Prophet (hadith), and the views of classical and contemporary scholars related to children's rights and parental responsibilities. The results of the study show that Islam places great emphasis on child protection as a trust that must be safeguarded. Children's rights in Islam include the right to life, the right to a clear lineage, the right to education, affection, financial support, and protection from physical and psychological abuse. Parents have both moral and religious obligations to ensure these rights are fulfilled. This study recommends strengthening the role of the family as the foundation of child protection within the framework of Islamic values, as well as fostering synergy between sharia principles and the positive legal system in order to establish a holistic and sustainable protection system for children.